PROFESSIONAL SOCIAL PSYCHOLOGICAL CHARACTERISTICS OF A PSYCHOLOGIST - Akbaraliyeva Asilaxon Tojiddinovna (Journals Park Publishing, 2024)
The article describes the psychological conditions that are implemented during the process of teaching psychological counseling to students, as well as the problem of professional growth of the psychologist, their structure, the characteristics of important professional qualities of local and foreign authors. we can see the professional and personal development of the student in mastering the approaches and this type of activity
Keywords: professional identity, intellectual potential, self-development, cognitive-semantic, emotional-volitional, behavior.